Fraud risk and trust on the intention to buy of e-commerce - Puspitarini, Dewi Anggun; Purnama, Prawira Aros; Dewi, Isti Riana (Journal of Contemporary Accounting, 2021)
This study aims to analyze and obtain empirical evidence of deceptive behavior as a moderating variable of trust in purchasing through e-commerce purchase intentions. The data of this research were obtained from the results of collecting a questionnaire of 100 respondents who were consumers who had made transactions through e-commerce sites. Testing the hypothesis in this study using the measurement model (Outer Model) and structural models (Inner Model) with the application of Partial Least Square (PLS). The PLS program used is SmartPLS version 3.02.8. The results of this study indicate that trust has a positive effect on purchase intentions. However, with deceptive behavior as moderation, deceptive behavior weakens the relationship between trust in purchasing through E-Commerce and purchase intention as a mediating variable. Purchase intention is proven to be a mediating variable that mediates trust in mentally buying. The government should be more assertive in handling cases of e-commerce crime that are rife to create security and comfort for e-commerce site users.